Seismic Response Analysis and Control of Frame Structures with Soft First Storey under Near-Fault Ground Motions - Chunyang Liu; Peng Sun; Ruofan Shi (Advances in Civil Engineering)
This paper proposes two kinds of arrangements of buckling-restrained brace dampers to strengthen soft-first-storey structures locally. Two types of near-fault ground motion, with and without pulse, were selected for a study of the seismic response characteristics of soft-first-storey structures with and without buckling-restrained brace dampers, and the effects of different bracing arrangements on improving the seismic performance of soft-first-storey structures were recognized. The results show that, compared with pulse-free ground motion, near-fault pulsed ground motion results in a more severe seismic response in soft-first-storey frame structures, leading to more serious and rapid destruction of the main structure. Buckling-restrained brace dampers have an obvious energy dissipation effect, play a better role in protecting the main structure, and have good practicality. Compared with structures in which the buckling-restrained brace dampers are arranged only on the bottommost layer, the bottom-four-layer-support structure is more advantageous in terms of seismic performance.